Australian Writers, British Publishers, 1870-1902. - Trainor, Luke (Australian Historical Studies, 2006)
In the late nineteenth century Australian writers were frequently part of a care group of advocates of on Australian cultural nationalism but they faced a particular problem. British publishers were dominant in book sales in Australia and could be unsympathetic to their aspirations. The writers made attempts to break into the British market, encouraged by the rhetoric of imperial understanding but, as the case of Macmillan and Co. illustrates, support could be difficult to secure, short-term and focused on quite different goals. Rolf Boldrewood had some success but that was owing to particular circumstances. In the first decades of the new century reliance would have to remain based on serial publication and emerging local book publishers.